Ukrainian Antarctic research: current bibliography and major trends in their evolution (2016–2017) - Videnina, N.G.; Rybachuk, V.P.; Fedchuk, A.P.; Prymachenko, S.I.; Petrenko, N.S. (Український антарктичний журнал, 2017)
Оbjectives of the study: to create a bibliography of scientific works of Ukrainian scientists and specialists on Antarctic research for the period 2007–2017. Bibliographic support and scientometric monitoring of the implementation of the State Special-Purpose Research Program in Antarctica for 2011–2020. Promoting the dissemination of scientific, popular scientific as well as other information about the activities of Ukraine in the Antarctic region of the planet. Мета роботи: створення бібліографії наукових праць українських учених і фахівців щодо дослідження Антарктики за період 2007–2017 рр. Бібліографічний супровід та наукометричний моніторинг виконання Державної цільової науково-технічної програми проведення досліджень в Антарктиці на 2011-2020 роки. Сприяння поширенню наукової, науково-популярної та іншої інформації щодо діяльності України в Антарктичному регіоні планети. Цель работы: создание библиографии научных трудов украинских ученых и специалистов по исследованию Антарктики за период 2007-2017 гг. Библиографическое сопровождение и наукометрический мониторинг выполнения Государственной целевой научно-технической программы проведения исследований в Антарктике на 2011-2020 годы. Содействие распространению научной, научно-популярной и другой информации о деятельности Украины в Антарктическом регионе планеты.